VAT Treatment of Financial Institutions - BAYDUR, Ismail (Institutional Knowledge at Singapore Management University, 2017)
This paper studies the effects of exempt treatment of financial services under a VATsystem. We develop a general equilibrium model with elastic labor supply, endogenous entry, anda banking sector. The banking sector provides loan services to producers and payment servicesto consumers. Our model display three key distortions under exempt treatment: (i) self-supplybias in the banking sector, (ii) consumption distortions, (iii) input distortions and tax cascading.Then, we calibrate our model to match the salient features of the tax system EU countries. Atax neutral policy regime switch from exempt treatment to full-taxation in loan services improveswelfare about 4%. Shutting down the entry margin has even bigger welfare gains. The same policyexercise for payment services also implies welfare gains and these gains greater than zero rating ofpayment services.